PEMBERDAYAAN MASYARAKAT PESISIR MELALUI INOVASI SMART IOT DRYING SYSTEM: SISTEM PENGERING TERKONTROL UNTUK PRODUKSI OLAHAN IKAN TONGKOL DI GAMPONG DEAH RAYA, BANDA ACEH - Eliana, Eliana; Rizki Julia Utama; Ferdi Nazirun Sijabat; Sari Varadilla Asiah; M.Julianda Phonna; Amazultul Zona (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
A small-scale industry group, "Anugrah," in Gampong Deah Raya, Banda Aceh, is facing challenges in producing processed skipjack tuna. Their conventional sun-drying method leads to inefficient production, with a long processing time of 3-5 days and inconsistent product quality. To solve this, a community empowerment program is proposed, centered on the innovative Smart IoT Drying System. This system is designed to monitor temperature and humidity in real-time, which will accelerate the drying process and ensure better, more consistent product quality. The program also includes training on product diversification and digital marketing to build the business capacity of the partner group. It is hoped that this program will boost production efficiency, expand market reach, and significantly increase the income of the coastal community in Gampong Deah Raya.